P81 Higher detection rate of lynch syndrome in patients with endometrial cancer by assessment of mismatch repair deficiency. (1st November 2019) - Pauly, N; du Bois, A; Harter, P; Prader, S; Rhiem, K; Schömig-Markiefka, B; Heikaus, S; Heitz, F; Schneider, S; Baert, T; Traut, A; Ehmann, S; et al.
Abstract : Introduction/Background: Endometrial cancer (EC) is the most common gynaecologic malignancy in Europe. A hereditary background by germline mutations in the DNA mismatch repair (MMR) genes ( MLH1, MSH2, MSH6, and PMS2 ) as part of Lynch syndrome (LS) is expected in 2–4% of all EC. For women with LS, the lifetime risk of developing EC is up to 60%, which is higher than colorectal cancer risk. EC is considered a sentinel cancer of women with LS, making its proper diagnostic workup key in the detection of LS and prevention of other cancers. Detection of affected women by Amsterdam II, revised Bethesda criteria has low sensitivity. Up to 30% of EC are MMR deficient (MMRd) which is caused in part by germline mutations. Methodology: We analysed 231 consecutive EC patients treated at Kliniken Essen-Mitte. MMR was either assessed on paraffin-embedded tumour slides by immunohistochemistry (IHC), PCR based microsatellite analysis or both. In case of MLH1 ± PMS2 deficiency or microsatellite instability additional methylation analysis was performed. Amsterdam II, revised Bethesda criteria and PREMM5 Model were used to detect patients with a familial history at risk for LS. Results: MMR diagnostic was successfully performed in 213 patients (110-IHC, 69-PCR, and 34-both). MMRd was detected in 45 patients (21.2%). We observed no discordant results between IHC and PCR. Methylation analysis was performed in 75, 5% (n=34) of MMRd EC resulting in the identification of 12 patients at risk for LS. The Amsterdam II and Bethesda criteria identified none of these patients. The PREMM5 Model proposed further investigation in seven of these patients. Genetic testing was performed in five patients and revealed two mutation carriers. Conclusion: General MMRd assessment is a feasible strategy to improve the detection of LS in patients presenting with endometrial cancer as an additional measure to familial history. Disclosure: NP has nothing to disclose. BA received fees/honoraria (e.g. lectures, advisory boards) from Roche, Amgen, Astra Zeneca, Tesaro, Clovis, Celgene, and non-financial support (e.g. travel grant) from Roche, PharmaMar, Tesaro outside the submitted work. AdB received honoraria for advisory boards outside the submitted work from Roche, Clovis, Astra Zeneca, Tesaro, Pfizer, Pharmar, Biocad and Genmab.PH received: Honoraria: Astra Zeneca, Roche, Sotio, Tesaro, Stryker, ASCO, Zai Lab, MSD Advisory Board: Astra Zeneca, Roche, Tesaro, Lilly, Clovis, Immunogen, MSD/Merck; Research funding (Inst): Astra Zeneca, Roche, GSK, Boehringer Ingelheim, Medac, DFG, European Union, DKH, Tesaro, Genmab.SP has nothing to disclose.KR has nothing to disclose. FH has received Advisory board: Roche, Tesaro, Honoraria: AstraZeneca, Roche, Tesaro, Clovis, travel/accommodation expenses: PharmaMar; Tesaro.TB has reported research grant from Amgen, travel expenses from Amgen and Roche as well as advisory board membership for Tesaro. BSM has nothing to disclose. SS has received fees/honoraria (e.g. lectures, advisory boards) Tesaro, Astra Zeneca, Roche and travel grant from Tesaro outside the submitted work. SH has nothing to disclose.SE has nothing to disclose. AT has nothing to disclose.